2019
DOI: 10.1063/1.5093674
|View full text |Cite
|
Sign up to set email alerts
|

Combined plasmon-resonance and photonic-jet effect in the THz wave scattering by dielectric rod decorated with graphene strip

Abstract: We consider the scattering of an H-polarized plane wave by an infinite dielectric rod with a conformal graphene strip of arbitrary angular width, placed at the rod rear side. Our analysis is based on the hypersingular integral equation for the current induced on the strip. Discretization of this equation is carried out by the Nystrom-type method, which has a guaranteed convergence. This meshless trusted computational instrument enables us to plot the dependences of the absorption cross-section (ACS) and the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 30 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…As known, a strip of graphene can be considered as a plasmon surface wave Fabry-Perot resonator [12,16,21].…”
Section:    mentioning
confidence: 99%
See 2 more Smart Citations
“…As known, a strip of graphene can be considered as a plasmon surface wave Fabry-Perot resonator [12,16,21].…”
Section:    mentioning
confidence: 99%
“…Both flat and curved graphene strips attract attention today as easily fabricated tunable components of plasmonic antennas, waveguides, and sensors [11][12][13][14][15]. Recently, in [16] it was shown that a resonance graphene strip placed into the EMJ area of a circular dielectric rod enhances greatly the near field without increasing the radius or refractive index. Guided by the reciprocity principle, in this work we consider the radiation a THz range line magnetic current in the presence of a circular dielectric rod, decorated with a conformal strip of graphene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In (38)-(39) symbol δ qp is the Kronecker delta. Taking into account (35), (38) from equation (27) we obtain:…”
Section: Systems Of Integral Equationsmentioning
confidence: 99%
“…Then the electrical conductivity model developed for infinite graphene surfaces can be used, supplemented with the condition of local power finiteness. Besides, in the THz frequency range, graphene conductivity can be considered isotropic since the characteristic size of the hexagonal structure of graphene is about 10 nm [34]. In the absence of magnetostatic doping and in the considered frequency range, graphene conductivity σ can be expressed in the form of scalar function of frequency f, chemical potential μ c , electron relaxation time τ, and temperature T. It can be obtained from the Kubo formalism [5].…”
Section: Introductionmentioning
confidence: 99%